MANAGEMENT OF BOYS WITH UNDESCENDED TESTES - Robert Kodrič; Jernej Strojinc; Mateja Jakopec (The Society for Children with Metabolic Disorders, 2020)
Cryptorchidism is one of the most common birth defects in newborn boys. The risk factors are prematurity and low birth weight. The diagnosis is clinical; diagnostic imaging does not significantly influence the decision for further treatment. Surgery is the treatment of choice. It is recommended that boys undergo surgery between 6 and 12 months of age and by the age of 18 months at the latest. Bilateral cryptorchidism is present in 30% of cases and it has a negative impact on fertility. Boys who have been treated for cryptorchidism are advised to examine themselves later in life because of the higher likelihood of developing testicular cancer.